Control de bienes de larga duración del distrito 12d01 Baba Babahoyo Montalvo – Educación - Núñez Acosta, Miguel Ángel (2020)
The present study was carried out with the purpose of analyzing and knowing the control of the long-term assets of the District Directorate 12D01 BABA BABAHOYO MONTALVO - EDUCACION, The methodology was descriptive. It was used for the collection of the information to the Administrative District analyst, responsible for the assets of District Directorate 12D01, the results showed that the winery does not have the control allows it to effectively carry out the activities of reception, entry and registration of the Long-term assets in the Esbye system.